Analysis of a Sensor using Rician k-factor for Identification of a Spherical Conductor Submerged in Soil - Yoiyod, P.; Pathoumvanh, S.; Phongcharoenpanich, C.; Krairiksh, M. (My University, 2018)
The Unexploded Ordnance (UXO) problem is a barrier plaguing for the country's development since the UXO contamination can render lands unusable. The UXO is defined as a metallic material submerged into the soil. Generally, the clearance team uses a handheld metal detector for scanning sub-surface and sensing the location of such a bomb. This outdated method is labor intensive and time consuming when scanning in the large area. Hence, the high-speed and lightweight scanning system for sensing underground object is desired. This paper investigated a feasibility to develop a Ground Penetrating Radar (GPR) system that can detect metallic bombs which is submerged in soil at the depth of 30 cm from the surface. The scattered waves from an object were calculated at different positions and the Rician k-factor was estimated from the ratio of mean to variance. The position with highest k-factor indicates the location of the target UXO.
Keywords: GPR; Monostatic radar; Rician k- factor; submerged spherical conductor